2020
DOI: 10.1016/j.spinee.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of discogenic cells, an investigational cell therapy for disc degeneration

Abstract: BACKGROUND/CONTEXT: Disc degeneration (DD) is a significant driver of low back pain and few treatments exist to treat the pain and disability associated with the disease. PURPOSE: Our group has developed a method to generate therapeutic discogenic cells as a potential treatment for symptomatic DD. These cells are derived and modified from adult nucleus pulposus cells. In this study, we evaluated the characteristics, mode of action, and in vivo efficacy and safety of these cells prior to human clinical testing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 44 publications
2
59
0
Order By: Relevance
“…109 There has also been a preclinical study using preconditioned cells from the NP of human IVD tissue, called discogenic cells, with promising outcomes. 110,111 These are cells extracted from NP tissue and expanded in a proprietary cocktail of supplements before insertion into degenerative IVD tissue. Preclinical studies demonstrated the ability of discogenic cells to significantly partially restore lost disc height and improve morphology compared with vehicle or sham controls while demonstrating these cells are safe too.…”
Section: Preconditioningmentioning
confidence: 99%
“…109 There has also been a preclinical study using preconditioned cells from the NP of human IVD tissue, called discogenic cells, with promising outcomes. 110,111 These are cells extracted from NP tissue and expanded in a proprietary cocktail of supplements before insertion into degenerative IVD tissue. Preclinical studies demonstrated the ability of discogenic cells to significantly partially restore lost disc height and improve morphology compared with vehicle or sham controls while demonstrating these cells are safe too.…”
Section: Preconditioningmentioning
confidence: 99%
“…In a previous study, suppression of activated microglia/macrophages with minocycline or toxin-induced depletion of CX3CR1-positive microglia/macrophages protected rod cells against cell death in retinal degeneration (rd) 10 mice (135,136). However, attenuation of the homeostatic function of microglia by disrupting the CX3C chemokine ligand 1-CX3C chemokine receptor 1 axis or the complement component 3-complement receptor 3 axis accelerates rod degeneration, along with proinflammatory microenvironmental changes such as increased TNF-α and IL-6 levels (137,138). Therefore, microglia/macrophages have a bidirectional function in RP, as expected from the basic understanding of the interaction between cell death and inflammation.…”
Section: Functional Roles Of Inflammatory Response In Cone Cell Deathmentioning
confidence: 99%
“…During the growth process, cells exhibit phenotypic changes from that of cells found in the native disc tissue. Specifically, the cells lose expression of CD24 (44), which is a marker for nucleus pulposus cells (45). Also, Discogenic Cells have a unique surface marker expression profile that includes high expression of CD73, CD90, and HLA-ABC and a low expression of CD34 and HLA-DR/DQ/DP (44).…”
Section: Overview Of Injectable Disc Cell Therapy (Idct) and Immunomomentioning
confidence: 99%
“…Specifically, the cells lose expression of CD24 (44), which is a marker for nucleus pulposus cells (45). Also, Discogenic Cells have a unique surface marker expression profile that includes high expression of CD73, CD90, and HLA-ABC and a low expression of CD34 and HLA-DR/DQ/DP (44). The cells generate the extracellular matrix found within native intervertebral disc tissue, including proteoglycan and collagen.…”
Section: Overview Of Injectable Disc Cell Therapy (Idct) and Immunomomentioning
confidence: 99%